Popularyzacja czytelnictwa w szkole. Storytelling (gawędziarstwo), booktalking (opowiadanie o książkach) i głośne czytanie - Matwiejczuk, Agnieszka (Dydaktyka Polonistyczna, 2016)
The main aim of the article was to characterize various ways of popularizing reading amongstudents. The possible usage of storytelling, booktalking and loud reading with children and teenagers was pinpointed as the effectiveness of these methods was emphasized in the research. Whatis of special importance in bringing reading to general use is the relationship between all schoolentities responsible for pupils’ development. Studies conducted by the National Library of Polandand the Educational Research Institute indicated that the number of readers is decreasing every year.Moreover, some social events aiming at changing this phenomenon (among both children and adults)were mentioned.